2023
DOI: 10.1021/acs.est.2c09372
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic Acid (PFOA) Incorporated into Iron Particles Promoted the Formation of Disinfection Byproducts under Drinking Water Conditions

Abstract: Perfluorooctanoic acid (PFOA) is an emerging persistent organic pollutant that is frequently detected throughout the drinking water supply system. Here, we first found that PFOA could significantly increase the formation of disinfection byproducts (DBPs) in unlined iron pipes (UIPs) during the distribution process. The increased DBPs were not due to the reaction of PFOA itself with free chlorine, but the in situ formed Fe–PFOA complex played a key role. Notably, PFOA could enhance iron release from UIPs and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…For DBP formation, iron oxides have a catalytic effect with the formation of • OH to break large natural organic matter (NOM) compounds into small molecules with higher reactivity . The formation of Fe-perfluorooctanoic acid complex has been found to have an even stronger catalytic effect for DBP formation than single iron crystals . Moreover, iron particles could release NOM during boiling, which further affects DBP formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For DBP formation, iron oxides have a catalytic effect with the formation of • OH to break large natural organic matter (NOM) compounds into small molecules with higher reactivity . The formation of Fe-perfluorooctanoic acid complex has been found to have an even stronger catalytic effect for DBP formation than single iron crystals . Moreover, iron particles could release NOM during boiling, which further affects DBP formation .…”
Section: Introductionmentioning
confidence: 99%
“…18 The formation of Fe-perfluorooctanoic acid complex has been found to have an even stronger catalytic effect for DBP formation than single iron crystals. 19 Moreover, iron particles could release NOM during boiling, which further affects DBP formation. 20 Previous research has found that the concentrations of aromatic DBPs during boiling generally followed an increasing trend due to decarboxylation of polycarboxylic precursors in chlorinated tap water.…”
Section: Introductionmentioning
confidence: 99%
“…With carboxyl groups, PFOA can bind with metal ions through complexation and guide the formation of composite particles . In our previous study, we found that PFOA itself could not react with chlorine to generate disinfection byproducts (DBPs), but DBP precursors with aromatic structures were favorable for forming strong Fe–π interactions with the Fe–PFOA complex, resulting in more • OH for the formation of toxic aromatic DBPs, which provided a new perspective on the risk of PFOA …”
Section: Introductionmentioning
confidence: 99%
“…5 In our previous study, we found that PFOA itself could not react with chlorine to generate disinfection byproducts (DBPs), but DBP precursors with aromatic structures were favorable for forming strong Fe−π interactions with the Fe−PFOA complex, resulting in more • OH for the formation of toxic aromatic DBPs, which provided a new perspective on the risk of PFOA. 6 In DWDS, a biofilm could be formed on the interface of the pipe wall. Self-produced extracellular polymeric substance (EPS) could accumulate organics and inorganics to form a biofilm matrix by providing viscous forces between bacteria and the pipe wall.…”
Section: Introductionmentioning
confidence: 99%
“…Zhuang et al reported that nitrate promotes the formation of toxic N-DBPs in corroded iron drinking water pipes. 107 Results suggested that a Fe−O−C bond forms between iron corrosion products and NOM, which promotes electron transfer for nitrogen transformation with pyrrolic nitrogen as the intermediate species. Density functional theory (DFT) calculations supported this proposed mechanism.…”
mentioning
confidence: 99%